If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -11(x + 9) = 99 Reorder the terms: -11(9 + x) = 99 (9 * -11 + x * -11) = 99 (-99 + -11x) = 99 Solving -99 + -11x = 99 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '99' to each side of the equation. -99 + 99 + -11x = 99 + 99 Combine like terms: -99 + 99 = 0 0 + -11x = 99 + 99 -11x = 99 + 99 Combine like terms: 99 + 99 = 198 -11x = 198 Divide each side by '-11'. x = -18 Simplifying x = -18
| 6x^4*3x^4= | | y=-0.80(55)+136 | | 4.3*p=28.81 | | 5n-9=71 | | 5(x+4)=75 | | 6y-7=10y+25 | | y=-0.80(45)+136 | | 7(1y+-2)+8=3(1y+-4)+-2 | | y=-0.80(35)+136 | | -18-6k=6(13k) | | 2x-1=-x+5 | | 15x^3-7x-2= | | x+29=83 | | 16/7=m/21 | | 3x+5=-6 | | 0.2x-1.5=0.1 | | 3a^2+4=0 | | 16-5(3t-4)=8-(-2t+11) | | -7(-5x+7)=-49 | | 4m-4=9m | | 29=17-2x | | 3y+5=y | | 6(-6x-10)=-132 | | 3(x+1)+7(x+1)-6= | | 8x=8x+6 | | 0.5(x+4)-(10x+9)=-77 | | -4(1x+10)=-32 | | 25+15=x | | .33(3x+6)=8x+10 | | -6=-5x+6 | | 9-2+5=260 | | 0.5(x+4)-(10x+9)=-65 |